2017
DOI: 10.1111/cns.12767
|View full text |Cite
|
Sign up to set email alerts
|

Preventive and therapeutic potential of ascorbic acid in neurodegenerative diseases

Abstract: In this review, we summarize the involvement of ascorbic acid in neurodegenerative diseases by presenting available evidence on the behavioral and biochemical effects of this compound in animal models of neurodegeneration as well as the use of ascorbic acid as a therapeutic approach to alleviate neurodegenerative progression in clinical studies. Ascorbate, a reduced form of vitamin C, has gained interest for its multiple functions and mechanisms of action, contributing to the homeostasis of normal tissues and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(57 citation statements)
references
References 62 publications
0
56
0
1
Order By: Relevance
“…Ascorbate can easily enter the brain through the glucose transporter (GLUT1) when a considerable amount of DHA is present in the blood. Ascorbate or DHA in the cerebrospinal fluid enters the neuron via sodium-dependent transporter-2 (SVCT-2) or GLUT1 transporters [ 130 , 131 ]. Once they enter the neuron, DHA can be reduced to ascorbate or released by GLUT1.…”
Section: Role Of Antioxidants In the Brainmentioning
confidence: 99%
“…Ascorbate can easily enter the brain through the glucose transporter (GLUT1) when a considerable amount of DHA is present in the blood. Ascorbate or DHA in the cerebrospinal fluid enters the neuron via sodium-dependent transporter-2 (SVCT-2) or GLUT1 transporters [ 130 , 131 ]. Once they enter the neuron, DHA can be reduced to ascorbate or released by GLUT1.…”
Section: Role Of Antioxidants In the Brainmentioning
confidence: 99%
“…88 It is interesting, however, that the huntingtin gene plays a role in the translocation of the ascorbate transporter to the plasma membrane, leaving open the possibility of a disruption in cellular storage of ascorbate. 89 Although a 3-day injection regimen of sodium ascorbate (300 mg/kg/d) in R6/2 mice restored striatal extracellular ascorbate to WT levels and improved striatal function, 40 such a high dose is unlikely to be an effective long-term treatment solution, especially in light of stringent control of ascorbate entry into brain tissue from blood. 31 At this point, the bulk of the evidence indicates that the ascorbate problem in HD is one of release, which links it directly to down-regulation of GLT-1.…”
Section: Ascorbate and The Glutamate Uptake Problemmentioning
confidence: 99%
“…This result differs from that reported by Floriano et al [5] who found that 5 of the 20 diets analyzed had lower values of vitamin A than the recommended level. Excess vitamin C, as found in the intermittent fasting and gluten-free diets, causes diarrhea, urinary oxalate excretion and formation of renal calculus [24], whereas its deficiency, as found in the low-carb diet, is associated with neurodegenerative diseases including Alzheimer's, Parkinson's and Huntington's diseases, multiple sclerosis and amyotrophic lateral sclerosis [25]. In the studies of Floriano et al [5] and Abreu et al [12], 80% and 82% of the analyzed diets, respectively, had adequate levels of vitamin C. Similarly, Marangoni & Maniglia [22] found adequate vitamin C levels in their study, as recommended by the DRI.…”
Section: R E S U L T S a N D Discussionmentioning
confidence: 99%